Green-light fundus autofluorescence in diabetic macular edema - Reznicek, Lukas (International Journal of Ophthalmology Press, 2013)
AIM: To evaluate the role of central green-light fundus autofluorescence (FAF) in diabetic macular edema (DME). METHODS: A consecutive series of 92 study eyes with diabetic retinopathy were included. Out of those, 51 diabetic eyes had DME and were compared to 41 diabetic eyes without DME. In all subjects, green-light FAF images were obtained, quantified and classified into various FAF patterns. Cross-sectional optical coherence tomography (OCT) scans were obtained for evaluation of Inner/Outer segment (IS/OS) layer integrity, measurements of central RPE-IS/OS layer thickness as well as classification of DME into various subtypes. RESULTS: Mean central green-light FAF intensity of eyes with DME (1.289±0.140)log did not significantly differ from diabetic patients without DME (1.317±0.137)log. Most classifiable FAF patterns were seen in patients with cystoid DME. Mean central retinal thickness (CRT) of all study eyes with DME was (501.9±112.4)µm compared to (328.2±27.0)µm in diabetic patients without DME. Patients with DME had significantly more disrupted photoreceptor IS/OS layers than diabetic patients without DME (28/51 vs 5/41, P<0.001). Mean RPE-IS/OS thickness of patients with DME (60.7±14.1)µm was significantly (P<0.001) lower than in diabetic eyes without DME (73.5±9.4)µm. Correlation analys1s revealed non-significant correlations of green-light FAF intensity and OCT parameters in all subtypes of DME. CONCLUSION: Our results indicate a poor correlation of central green-light FAF intensity with CRT, IS/OS layer integrity or RPE-IS/OS layer thickness in diabetic patients with or without DME and its various subtypes. Thus, central green-light FAF is not suitable for detection of retinal thickening in DME.